Mechanical properties of basalt: a study on compressive loading at different strain rates using SHPB - Jan Falta; Nela Krčmářová; Tomáš Fíla; Martin Vavro; Leona Vavro (Acta Polytechnica CTU Proceedings)
This article focuses on the mechanical properties of basalt in compressive loading at different strain-rates. The study employs advanced instrumentation for the evaluation of the results in dynamic conditions, while standard uni-axial loading device is used for evaluation in quasi-static conditions. Basalt specimens were subjected to four different loading-rates from 200–600 s−1 on which the stress-strain dependence was evaluated together with DIC analysis of crack initiation and disintegration process. Understanding the mechanical properties of basalt can provide insights for engineers and designers in creating structures that are durable and able to withstand different loading conditions. The findings of this study can have implications for a wide range of industries, including aerospace, automotive, and construction, among others.